Asuhan Kebidanan Pada Ibu Hamil dalam Mengatasi Nyeri Punggung - fitriahadi, enny (Sahabat Publikasi Kuu, 2024)
Pain is a very common problem in pregnancy, especially in the second and third trimesters of pregnancy. Pain causes fear and anxiety so that it can increase stress and drastic physiological changes during pregnancy. The research method used is a qualitative design with a participatory observational method with a case study approach. The location of the case study was at the PKU Muhammadiyah Hospital in Yogyakarta. The subject of the single case study was Mrs. D, 37 years old, G3P1A1 with a normal third trimester pregnancy, 33+5 weeks of gestation. The case study was carried out in March 2023. The data collection methods in this study were interviews, observations and documentation studies. After carrying out care for pregnant women in the third trimester with back pain, an analysis and management were obtained that influenced the care of Mrs. D. Results: after observation on March 15, 2023, Mrs. N found that the complaints of back pain felt had decreased. Suggestion: It is hoped that mothers will actively ask midwives about the complaints they feel or seek information from accurate sources.